Foldable Structure Based On Origami With Curved Fold Lines Concept - Ng, Wai Keun (2018)
Origami with curved fold lines possesses characteristic feature of curved surface bounded by curved fold lines which can be advantageously adopted for foldable structures. However, potential use of origami with curved fold lines has not been much studied due to complexity of the folding process under many different possible layouts and configurations of curved fold lines. This study is carried out to investigate the characteristics of the folding process of origami with curved fold lines. Effect of surface geometry at different folding stage of origami with curved fold lines on structural behaviour of shell structure with curved fold lines (SSCFL) was also determined. A set of criteria in classifying origami with curved fold lines created by many researchers or origami scientist has been established and used in the classification of 51 origami models into 11 groups. From the 51 models, 13 number of origami models with potential application as foldable structures have been chosen and regrouped into the following four main categories: Non-inflated n Degree-n Vertices (category A), Inflated n Degree-n Vertices (category B), n Mountain Ridge Curve (category C), and the Complex Shape (category D). 3-D surface data acquisition using optical non-contact measuring techniques of image capturing method and structured light method were used to obtain an accurate geometrical model of origami with curved folds. CAD based procedures in generating 3-D geometrical model of origami with curved fold lines have been developed. The folding mechanism based on the evaluation of a set of measurement or parameter representing change in surface geometry of the origami models during the folding process has been studied. From the results of measurements, it is found that folding process of origami under categories A and B is accompanied by twisting deformation about the center of the model. No twisting deformation is observed in folding process of origami under categories C and D. Models under category C (n Mountain Ridge Curve) specifically C10 shows the largest change in maximum height at center of model, and largest reduction in plan area of origami during folding process. Meanwhile, change in geometry in term of maximum angle of rotation of the center and boundary of origami model is found to occur in Model B06 under category B (Inflated n Degree-n Vertices). The maximum change in height at boundary is found to occur in Model B04. A series of SSCFL models with surface geometry of the respective origami model at different folding stage have been generated. These SSCFL are 100 times scaled up models of respective origami model with surface thickness of 200 mm (overall surface) and 250 mm (at support regions). The SSCFL were assigned with line supports and modelled using normal strength concrete. Results of finite element analysis under self-weight show that SSCFL models under category C (specifically surface geometry associated with C11 and C12) and category D (D13) satisfy stress limit due to their resemblance to dome structure. On the other hand, SSCFL models under categories A and B failed to satisfy stress limit due to unsymmetrical nature of the surface geometry and existence of free boundary of structure with relatively large overhang length. SSCFL models were found to exhibit superior performance in terms of stiffness due to existence of curved folds which increases the effective depth of the structure.